2019
DOI: 10.3389/fmicb.2019.01474
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling of Gaeumannomyces graminis var. tritici in Wheat Roots in the Absence and Presence of Biocontrol Bacillus velezensis CC09

Abstract: This study aimed to explore potential biocontrol mechanisms involved in the interference of antagonistic bacteria with fungal pathogenicity in planta . To do this, we conducted a comparative transcriptomic analysis of the “take-all” pathogenic fungus Gaeumannomyces graminis var. tritici ( Ggt ) by examining Ggt -infected wheat roots in the presence or absence of the biocontrol agent Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
(71 reference statements)
0
18
0
2
Order By: Relevance
“…An aminotransferase was also overexpressed in G . tritici grown on PDA medium [ 37 ]. Concerning the genes driving the ‘oxydoreductase activity’ enrichment ( S8B Table ), study in Magnaporthe oryzae showed that the methylmalonate-semialdehyde dehydrogenase regulated pathogenesis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An aminotransferase was also overexpressed in G . tritici grown on PDA medium [ 37 ]. Concerning the genes driving the ‘oxydoreductase activity’ enrichment ( S8B Table ), study in Magnaporthe oryzae showed that the methylmalonate-semialdehyde dehydrogenase regulated pathogenesis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, G. tritici transcriptomics study in host plant grown in soils of different pH would be interesting to focus more precisely on the infection stage. At this time indeed, only one transcriptomics studies were performed in G. tritici [37,53], and one highlighted that over 3,000 genes (including genes involved in signal transduction pathways, development, plant cell wall degradation, and response to plant defense compounds) were differentially expressed between G. tritici in culture and G. tritici infecting roots, but this study is based on a single strain not characterized for G1/G2 type [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. velezensis can produce volatile organic compounds (VOCs), iturin, fengycin, surfactin, and antibiotics, among others, to inhibit fungal growth (Jin et al, 2017). Bacteria can also inhibit the growth of fungi by altering the gene expression of the fungus (Kang et al, 2019). At the same time, bacteria can produce indole acetic acid (IAA), siderophore, and phosphorus solubilization to promote plant growth (Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%